New techniques for breeding maize (Zea mays) varieties with fall armyworm resistance and market‐preferred traits for sub‐Saharan Africa. (18th November 2022) - Matova, Prince M.; Kamutando, Casper N.; Warburton, Marilyn L.; Williams, W. Paul; Magorokosho, Cosmos; Shimelis, Hussein; Labuschagne, Maryke; Day, Roger; Gowda, Manje
Abstract: Deploying maize varieties with fall armyworm ( Spodoptera frugiperda [J.E. Smith]; FAW) resistance, desirable product profiles (PPs) and climate resilience is fundamental for food and economic security in sub‐Saharan Africa (SSA). This study reviewed and identified challenges and opportunities for effective and accelerated breeding of demand‐led maize hybrids with FAW resistance and adaptation to the diverse agro‐ecologies of SSA. Lessons were drawn on improving breeding efficiency through adequate genetic variation delivered via prebreeding programmes, speed breeding and a reduced breeding stage plan. Appropriate PPs aligned with demand‐led breeding approaches were highlighted as foundations for variety design and commercialization. Challenges to accelerated FAW resistance breeding in maize included inadequate funds and modern tools; poor adaptation of some exotic donor parental lines; lack of information on FAW resistance among local varieties; lack of integration of molecular markers associated with FAW resistance and agronomic traits into selection plans; and limited infrastructure for FAW rearing and germplasm screening. Integration of modern breeding tools and scientific innovations were recommended for accelerated development and release of FAW resistant and market‐preferred maize varieties.